A first computation of three-loop master integrals for the production of two off-shell vector bosons with different masses - Dhimiter Canko; Mattia Pozzoli (Journal of High Energy Physics)
Abstract We present analytic results on physical kinematics for four integral families that are relevant to the production of two off-shell vector bosons with different masses. Our study consists of a ladder-box, a tennis-court, and two reducible ladder-box-like families. The results for the master integrals of these families are expressed up to order six in the dimensional regulator in terms of real-valued multiple polylogarithms. Furthermore, a semi-numeric solution is provided, employing generalized power series expansions using the package DiffExp.